Interpolyelectrolyte Complexes Based on Eudragit® Copolymers as Carriers for Bioadhesive Gastroretentive Metronidazole Delivery System - D. S. Gordeeva; A. V. Sitenkova (Bukhovets); R. I. Moustafine (Разработка и регистрация лекарственных средств, 2020)
Introduction. There are a number of drugs, the absorption zone of which is the upper region of the gastrointestinal tract (GIT) – the stomach and duodenum. To increase bioavailability, gastroretentive (intragastric) systems for the controlled drug delivery are being developed. To date, there are various approaches to ensure intragastric drug delivery. One of the most promising approaches is the use of excipients with bioadhesive properties, both individually and in combination with other types of gastroretentive systems.Aim. Development and research of new carriers for gastroretentive bioadhesive drug delivery systems based on interpolyelectrolyte complexes (IPEC) with the participation of chemically complementary poly(meth)acrylates of the Eudragit®.Materials and methods. The study of swelling ability was carried out in a medium of 0.1 M hydrochloric acid solution (pH 1.2) at a temperature of 37 ± 0.5 °C for 6 hours. The study of the release of metronidazole (MZ) from matrices based on the corresponding IPEC was performed on a DFZ II instrument (ERWEKA, Germany) according to the Flow Trough Cell method in 0.1 M HCl medium, pH 1.2, flow rate 4 ml/min in a closed cycle within 6 hours. The amount of released MZ was estimated by UV spectrophotometry on a Lambda 25 instrument (PerkinElmer, USA) at a wavelength of 274 nm. IPEC adhesion was studied using a TA.XTplus texture analyzer (Stable Micro Systems, UK).Results and discussion. Matrices based on IPEC 1 were disintegrated after being in a medium with a pH of 1.2 for 4 hours, matrices based on IPEC 4 were dissolved in an acidic medium for 3 hours. At the same time, matrices based on IPEC 2 and IPEC 3 retain their shape throughout the experiment and are characterized by rather high values of the degree of swelling. IPEC samples are characterized by higher adhesion performance compared to individual copolymers. The release of metronidazole from matrices based on IPEC 1 occurs in accordance with Fick's law of diffusion; from the matrix based on IPEC 4, MZ is released according to the anomalous transport mechanism.Conclusion. IPEC 3 is promising for use as carrier for gastroretentive bioadhesive systems of controlled delivery of metronidazole.